The Impact Study of Electrical Vehicle Charging Stations Loading to Thailands Northeast Power System and DRG Integration Planning to Reduce Power Congestion - Narumon Wannoi; Chaisit Wannoi; Chompooin-Inwai Chai; Nirudh Jirasuwankul; Churirat Boonkhun (My University, 2023)
This article presents the impact study of electrical vehicle charging stations (EVCS) loading to the Thailand's North eastern power system.Main purposes of this paper are to find the maximum number of EVCS that can be loaded to power system and to rank the critical areas under EVCS load changing by using the repeated power flow calculation technique.Results from the calculation are for the integration planning of distributed renewable generators (DRG) to reduce system congestion.Typically, the critical areas are buses or devices that violate of system control limits.The system control limits are consisting voltage limit and load percentage limit of power transfer devices.All critical areas are needed to improve system stability and reduce system congestion for support the EVCS growing.In this study, The EVCS have been installed on main roads in Thailand's North-eastern area from Bangkok to Nong-Khai province with a length of 624 km.The EVCS were installed every 50 km, totally 11 stations, and connected to 115 kV substations in the system.The impact study results found that the system experienced with congestion problem on following elements: a) 11 critical buses at 115kV network, b) one critical bus at 230kV network and c) one transmission line is overload to 100 percent at 115kV network when each of EVCS station load increase to 30 MW.In addition, study results reveal that when installed DRG at the right and proper locations, these can reduce congestions situation, reduce system losses and enhance system stability.
Keywords: Electric Vehicles and Infrastructure